UMPSA Bridge Run attracts over 2000 participants - Mimi Rabita, Abdul Wahit (UMPSA, 2023)
PEKAN, 2 September 2023 - More than 2,000 participants crossed the Sultan Abu Bakar Bridge in Pekan during the UMPSA Pekan Bridge Run 2023, held in conjunction with the 21st Anniversary and the Rebranding of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), which took place recently.